Endodontic Emergencies Encountered in a Tertiary Dental Hospital during the Periods of Prelockdown, Lockdown, and Sequential Unlock Phases of the First Wave of COVID-19 in Ahmedabad City, India - Akshayraj Langaliya; Dolly Patel; Aarshvi Shah; Aravind Kumbhar; Jinali Shah; Sharan Shah; Ishan Bhatt; Dhruvisha Dayala; Rajmeet Singh Gill; Saloni Patel; Yatra Patel; Mandar Shah; et al. (Hindawi Limited, 2022)
Introduction. With the worldwide spread of SARS-CoV-2 infection, temporary suspension of all the elective dental procedures and an urgent shift to nonaerosol producing dental treatments were observed. This study provides a detailed description of emergency treatments provided in the Department of Endodontics at a tertiary healthcare centre during the period of prelockdown, lockdown, and sequential unlocking from March 1, 2020, to October 31, 2020. Methods. Access to General and Departmental OPD data along with treatment records was obtained and was segregated based on age, sex, and treatments performed. Treatments were divided into aerosol generating procedures (AGPs) and non-AGPs and further subdivided into palliative treatment (PT), pulp capping (PC), incision and drainage (ID), temporary filling (TF), pulpectomy (PU), and pulpotomy (PO). Data was analysed and subjected to chi-square test. Results. A total of 15052 patients approached general OPD during the period of 8 months of which 5698 (37.86%) were endodontic in origin and treatments offered were PT 858 (15.05%), PO 1560 (27.37%), PU 2018 (35.42%), TF 500 (8.78%), ID 164 (2.88%), and PC 598 (10.94%). Also, more females (57.28% (3264/5698)) visited the department as compared to males (42.72% (2434/5698)). Conclusion. The pandemic had turned the tables on over the people around the world, and it has become extremely necessary to rule out the emergencies needed to treat the patients accordingly shifting more towards non-AGPs compared to AGPs among the various age groups of the society.